Dinâmica espacial da murcha-de-ceratocystis em Khaya senegalensis A. Juss - Benso, Lucas Antonio [UNESP]; Pieroni, Lisandro De Proença [UNESP]; Kurokawa, Sara Yumi Sassamoto [UNESP]; Ciriello, Valeria; Pieri, Cristiane De [UNESP]; Flechtmann, Carlos Alberto Hector [UNESP]; Jesus, Waldir Cintra De; Furtado, Edson Luiz [UNESP] (Grupo Paulista de Fitopatologia, 2021)
The genus Khaya includes important forest species, whose wood is used mainly in the furniture industry and civil construction. Khaya senegalensis is one of the most cultivated species in Brazil. Ceratocystis wilt is one of the main diseases of this culture, offering a serious risk if not properly managed. However, no epidemiological studies have been conducted involving this pathology in K. senegalensis. The objective of this work was to characterize the spread of Ceratocystis wilt in K. senegalensis, using the Dynamics and Foci Structure Analysis technique (DFSA) and the Dispersion Index (DI). Three plots with 540 individuals each were installed inside a plantation of this species. The quantification of the disease was done annually from 2016 to 2018, with the elaboration of dispersion maps of diseased plants, which served as the basis for all the analyzes performed. According to DFSA, the aggregate pattern was observed in all plots and years evaluated, with disease foci showing isodiametric growth. However, using the ID technique, the pattern varied between random and aggregate, depending on the size of the quadrat used. Due to the size of the foci observed in the experimental area, the use of larger quadrats in the ID was recommended, which indicated an aggregate pattern in most plots. Thus, it was possible to conclude here was a tendency for the aggregation of diseased plants, with a probable participation of the pruning tool in the process of spreading and/or infection by the causal agent.

O gênero Khaya engloba importantes espécies florestais produtoras de madeira, cujo lenho é utilizado principalmente na indústria moveleira e na construção civil. Dentre os membros desse gênero, Khaya senegalensis é uma das espécies mais cultivadas no Brasil. A murcha-de-ceratocystis está entre as principais doenças dessa cultura, se tornando limitante caso não manejada adequadamente. Até o momento não foram conduzidos estudos epidemiológicos envolvendo essa patologia em K. senegalensis. O objetivo deste trabalho foi caracterizar a disseminação da murcha-de-ceratocystis em K. senegalensis, por meio da técnica de Análise da Dinâmica e Estrutura de Focos (ADEF) e do Índice de Dispersão (ID). Instalou-se três parcelas com 540 indivíduos cada no interior de um talhão puro dessa espécie florestal. A quantificação da doença foi realizada anualmente de 2016 a 2018, sendo elaborados mapas de dispersão das plantas doentes, os quais serviram de base para as análises. Pela ADEF, observou-se o padrão agregado em todas as parcelas e anos avaliados, com focos apresentando crescimento isodiamétrico. No entanto, pela técnica do ID, o padrão variou entre ao acaso e agregado, em função do tamanho do quadrat utilizado na análise. Pelo tamanho dos focos observados na área experimental, recomendou-se o uso de quadrats maiores no ID, que indicaram um padrão agregado na maior parte das parcelas. Pôde-se concluir que no patossistema estudado houve tendência a agregação das plantas doentes, com uma provável participação da ferramenta de poda no processo de disseminação e/ou infecção pelo agente causal.
Spatial dynamics of Ceratocystis wilt in Khaya senegalensis A. Juss
Keywords: African mahogany; epidemiology; dissemination; mogno africano; epidemiologia; disseminação